Unravelling the palaeobiology of the dinosaurian post crania and associated carnivore teeth from the early jurassic, Elliot formation in the Eastern Cape - Lee Logie, Jessica (Department of Biological Sciences, 2025)
The Elliot Formation of the Stormberg Group of South Africa ranges in age from the Late Triassic to the Early Jurassic. This stratigraphic unit bears a varied dinosaur assemblage, among which sauropodomorph dinosaurs are the most abundant. Sauropodomorpha are particularly well documented in the Upper Elliot Formation and are morphologically and taxonomically diverse. Specimen AM 6147, a large basal sauropodomorph, was excavated from the Barkley Pass, Eastern Cape, Elliot Formation of South Africa in 2013 by a joint team from the Albany Museum and the University of the Witwatersrand led by Dr Billy de Klerk. The specimen comprises post cranial material including ribs, gastralia, vertebrae of the mid-posterior section of the tail, and a complete left pes. Associated with the specimen are three teeth of contemporaneous carnivores. Here, we describe the skeletal anatomy of AM 6147 and assess its phylogenetic affinities by scoring our findings in a phylogenetic data matrix. We also attempt to identify the carnivorous taxa to which the associated teeth may have belonged, and the nature of the relationship between them and AM 6147. Our phylogenetic analyses reveal that this specimen belongs to the Massospondylidae and that it is recovered as a new taxon, Enkulusaura deklerki, based on a unique combination of plesiomorphic and derived features. Our findings suggests that the three associated carnivore teeth could possibly belong to two different theropod dinosaur, while the third tooth is likely from a crocodylomorph. In conclusion, this study of AM 6147 shows that it is a new large bodied Massospondylid from the Elliot Formation and provides a better understanding of the diversity of basal Sauropodomorpha in the Early Jurassic of South Africa. Furthermore, the associated teeth contribute insight into the ecological relationships between these contemporaneous taxa.